Gesundheit von Kindern und Jugendlichen aus Familien mit ungesichertem Aufenthaltsstatus im Vergleich zu Kindern mit und ohne Migrationshintergrund: Auswertung der KiGGS-Daten 2003-06 = The health of children and adolescents fromfamilies with insecure residence status compared to children with permanent residence permits : analysis of KiGGS data 2003–2006 - Wenner, Judith; Bozorgmehr, Kayvan (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2016)
BackgroundThe health of children and adolescents from families with insecure residence status could be poorer compared to other children with permanent residence permits in Germany due to exposure before and during flight. Their insecure residence status and their comparably low social status in the destination country may contribute towards access barriers to health care. However, selection effects might also lead to better health compared to other children in the destination country. This study compares the health status of children and adolescents with insecure residence status to that of other children with and without migration background in Germany.MethodsWe use data from the Health Interview and Examination Survey for Children and Adolescents (KiGGS). In multivariable logistic regression models we analyze the associations between children’s residence status and their subjective and mental health, as well as their utilization of emergency services and vaccination status while adjusting for the children’s social status and migration background.Results and conclusionAmong 17,245 children, 197 (1.1 %) had an insecure residence status. Adjusting only for age and sex, an insecure residence status is associated with poorer subjective health (OR=3.12 (2.07-4.94)), mental problems (OR=1.83 (1.16-2.87)), an incomplete vaccination status (OR=2.0 (1.33-3.0)) and the use of emergency health services (OR=2.28 (1.2-4.36)). After adjusting also for social and migration status, only the association with the use of emergency care remains significant (OR=2.53 (1.18-5.43)). This association possibly indicates barriers to the use of regular primary care services, which requires further research.
Gesehen am 24.10.2019